Faculty Senate, Agenda, November 20, 2003 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2003)
Valdosta State University. Faculty Senate, Agenda, November 20, 2003.
1 electronic document. Faculty Senate, Agenda, November 20, 2003. 5 pages. 261,465 bytes.
Keywords: Valdosta State University. Faculty Senate; Electronic records; Committees; Corporation reports